2012
DOI: 10.1016/j.lwt.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of Satureja montana L. essential oil on TBARS and color of mortadella-type sausages formulated with different levels of sodium nitrite

Abstract: a b s t r a c tThis study aimed to evaluate the effect of adding winter savory (Satureja montana L.) essential oil (EO) at concentrations of 7.80, 15.60 and 31.25 ml/g on color and lipid oxidation (TBARS) in mortadella-type sausages formulated with different sodium nitrite (NaNO 2 ) levels (0, 100 and 200 mg/kg) and stored at 25 C for 30 days. The EO was extracted by hydrodistillation and analyzed by gas chromatographyemass spectrometry (GCeMS). Twenty-six chemical compounds were identified; the most prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…Increased lightness has been reported in bologna made with fibre (Viuda-Martos et al 2010b); however, that effect seems to be associated with many factors, including the concentration and type of pigments, fibre content and type, and water content and hygroscopicity of the materials dissolved in the water matrix (Fernández-Ginés et al 2003;Viuda-Martos et al 2010a). The increase in redness (P<0.05) of the sample with added nitrite (CN) as compared with reformulated sausages (RC and RA) is consistent with the role played by additives in the redness/pinkness of products (Coutinho de Oliveira et al 2012). Zarringhalami et al (2009), observed no significant differences in a* when annatto was used as a nitrite replacer in hot dogs, similar to the ones formulated in our experiment.…”
Section: Texturementioning
confidence: 53%
See 2 more Smart Citations
“…Increased lightness has been reported in bologna made with fibre (Viuda-Martos et al 2010b); however, that effect seems to be associated with many factors, including the concentration and type of pigments, fibre content and type, and water content and hygroscopicity of the materials dissolved in the water matrix (Fernández-Ginés et al 2003;Viuda-Martos et al 2010a). The increase in redness (P<0.05) of the sample with added nitrite (CN) as compared with reformulated sausages (RC and RA) is consistent with the role played by additives in the redness/pinkness of products (Coutinho de Oliveira et al 2012). Zarringhalami et al (2009), observed no significant differences in a* when annatto was used as a nitrite replacer in hot dogs, similar to the ones formulated in our experiment.…”
Section: Texturementioning
confidence: 53%
“…Coutinho de Oliveira et al (2012) also observed a minor effect exerted on colour by other ingredients (such as oil) in bologna samples made without nitrites. Zarringhalami et al (2009) observed no significant differences in L* when all the nitrite was replaced by annatto.…”
Section: Texturementioning
confidence: 82%
See 1 more Smart Citation
“…Amiri (2011) S. macrostema Gutierrez (2013) and Gutierrez and Navarro (2010) S. montana Cavar et al (2008), Chrpova et al (2010), de Oliveira et al (2012, Giao et al (2009Giao et al ( , 2010Giao et al ( , 2012Giao et al ( , 2013, Grosso et al (2009b), Karaborklu et al (2011), Karamaouna et al (2013), Karpouhtsis et al (1998), Michaelakis et al (2007), and Tunc (1995a, 1995b Espaillat et al (1993) and Grosso et al (2010) (continued ) products, particularly those are highly oxidative and microbial sensitive. Discussion for the antimicrobial activity potential of Satureja species can be extended.…”
Section: S Macrosiphoniamentioning
confidence: 99%
“…The authors attributed this discoloration to binding with the iron component of myoglobin. Dliveira et al (2012) also reported a reduction in the redness in the mortadella-type sausages when Satureja montana L. essential oil was added. According to authors, the reduction in the redness can be explained by a possible interaction between nitrite and chemical components present in the antioxidant, making the nitrite unavailable to combine with myoglobin to produce the characteristic red color.…”
Section: Evaluation Of Color Parameters During Shelf-life Storagementioning
confidence: 90%